Cause Analysis and Countermeasures of Through Shakes in Foamed Concrete Subgrade - Xianbin Huang; Chenyang Liu; Yahong Wangren; Mingxing Wang; Yujiao Mei; Zongrong Xie; Man Liao (Advances in Civil Engineering)
The paper presents a new type of material—foamed concrete—adopted for expansion subgrade of the expressway. Intriguingly, the irregular through shakes appear on its top. The method combining the engineering case, theoretical analysis, and numerical simulation is employed to analyze its T-shaped and tree-shaped through shake. The research indicates that when the underground water table is high, cracks are easily seen on the top of step-shape foamed concrete due to buoyancy force. Under the concentrated load effect, the maximum displacement of 27.09 mm is observed on the top of the simply supported beam when elastic modulus is 200 MPa. The maximum principle tensile stress of 0.34 MPa also occurs on the top of the simply supported beam when elastic modulus is 200 MPa and 400 MPa, which is greater than tensile strength of foamed concrete of 0.31 MPa and 0.26 MPa at 7 d and 28 d, respectively. Thus, the adoption of a simply supported beam structure fits site through crack. To avert cracks on the top of foamed concrete in high groundwater table, the antibuoyancy measures should be adopted prior to construction of the upper bearing stratum. The study has expanded the application scope of subgrade and enriched theory of foamed concrete filled in high groundwater table, providing a significant reference to similar projects.